TANAH VULKANIK DI LAHAN KERING BERLERENG DAN POTENSINYA UNTUK PERTANIAN DI INDONESIA / Volcanic Soils in Sloping Dry Land and Its Potential for Agriculture in Indonesia - Sukarman Sukarman; Ai Dariah; Suratman Suratman (Jurnal Penelitian dan Pengembangan Pertanian, 2020)
Volcanic soil is soil developed from pyroclastic materials released during the volcanic eruption. Althought the soil is fertile, it is mostly occurred in steep sloping highland that is critical to landslide and volcanic eruption. This paper discussed the characteristics and distribution of volcanic soils in sloping dry land, completed with the potential and constraints of their use for agricultural development. This information supports the zonation program of agricultural commodities in Indonesia. Volcanic soils distributed on the islands of Sumatra, Java, Bali, Nusa Tenggara, North Sulawesi and North Maluku. Mostly characterized by black or brownish A horizon and yellowish B horizon, crumb soil structure, crumbly consistency, high organic matter content, and low bulk density. The primary mineral composed by hyperstein, amphibole, augite, andesine, volcanic glass, plagioclase, labradorite, olivine, sanidin, apatite and biotite. The secondary minerals are d allophane, imogolit, ferrihydrite, halloysite, kaolinite and gibsite. Soil reaction vary from very acid to neutral with medium nitrogen content (on average). The potential P is low except in volcanic soils in Java. The P retention is high. The Cation exchange capacity varies from moderate to very high. The morphological, chemical and physical properties are good for supporting plant growth, except for those with high P retention. The land suitability classes are very suitable (S1) to marginally suitable (S3) for highland horticultural crops (vegetables and fruits) and estate crop plantations (tea, arabica coffee, and quinine). The limiting factors are relief/slope/erosion hazard and low soil fertility. These limiting factors can be eliminated by applying good agricultural and conservation practices that balance between land sustainability and productivity aspects.Keywords: Volcanic soils, pyroclastic, characteristics, potential  AbstrakTanah vulkanik terbentuk dari bahan piroklastika hasil erupsi gunung berapi dan sebagian besar berada di dataran tinggi lahan kering berlereng sehingga rawan longsor. Makalah ini membahas karakteristik dan penyebaran tanah vulkanik pada lahan kering berlereng, serta potensi dan kendala pemanfaatannya untuk pengembangan pertanian. Informasi ini dapat digunakan untuk mendukung program pewilayahan komoditas pertanian di Indonesia. Tanah vulkanik menyebar di Sumatera, Jawa, Bali, Nusa Tenggara, Sulawesi Utara, dan Maluku Utara, sebagian mempunyai horison A berwarna hitam atau kecokelatan dan horison B berwarna kekuningan, struktur tanah remah, konsistensi gembur, kandungan bahan organik tinggi, dan berat isi rendah. Mineral primernya terdiri atas hiperstein, amfibol, augit, gelas vulkanik, plagioklas, olivin, sanidin, apatit dan biotit. Mineral sekunder tanah terdiri atas alofan, imogolit, ferihidrit, haloisit, kaolinit dan gibsit. Reaksi tanah bervariasi dari masam sampai netral, kandungan nitrogen tergolong sedang, kandungan P potensial rendah kecuali tanah vulkanik di sekitar kawasan gunung berapi di Jawa yang mengandung P dan retensi P tinggi. Kapasitas tukar kation tanah vulkanik tergolong sedang sampai sangat tinggi. Sifat morfologi, kimia, dan fisik tanah tersebut menunjang pertumbuhan tanaman, kecuali retensi P-nya tinggi. Tingkat kesesuaian lahan sangat sesuai (S1) sampai sesuai marjinal (S3) untuk usaha tani komoditas hortikultura dataran tinggi (sayuran dan buah-buahan) dan tanaman perkebunan (teh, kopi arabika dan kina) dengan faktor pembatas kondisi wilayah berlereng yang berpotensi erosi. Berdasarkan faktor pembatas tersebut maka komoditas dan teknologi yang diterapkan pada tanah vulkanik perlu mengacu pada tingkat kesesuaian lahan dan diikuti oleh usaha konservasi sejak awal agar tanah dapat digunakan untuk pertanian secara berkesinambungan.Kata kunci: Tanah vulkanik, piroklastika, karakteristik, potensi